Student Response Analysis and Conception: Simple Harmonic Motion in High School - Maison Maison; Astalini Astalini; Dwi Agus Kurniawan; Ayudiah Siahaan (EduResearch Mitra Inovasi, 2021)
Each student has different abilities in understanding physics lessons because the concepts of physics are both constructive and abstract. This research was conducted to determine the level of understanding of students' concepts and the relationship between students' responses to the use of four tier instruments. The research method used is a mixed method with an exploratory design. The research subjects were students of class XI IPA SMAN Titian Teras H. Abdurrahman Sayoeti. The sampling technique is probability sampling. Data collection was carried out qualitatively and quantitatively using material expert validation sheets, four tier diagnostic tests and student response questionnaires. Qualitative data analysis techniques with assessment of material expert validation sheets and quantitative data with correlation test. The results of data processing obtained that the validator's assessment of the four tiers was 91.25% in the very good category, the correlation test was carried out between the questionnaire and the instrument, the significance result was 0.000 and the Pearson correlation was 0.753, which means it has a strong relationship and its use is responded well by students, the percentage is 97%.